PELATIHAN KOMPUTER BAGI MASYARAKAT PENYANDANG DISABILITAS - Halim Budi Santoso; Argo Wibowo; Rosa Delima; Antonius Rachmat C; Jong Jek Siang (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Disable Person Organization Mitra Sejahtera (DPO Mitra Sejahtera) is an organization for disable people and found by Christian Public Health Foundation (YAKKUM) in Yogyakarta, especially in some areas in Gunung Kidul, Bantul, and Kulon Progo, Special Region of Yogyakarta. This organization focuses on empowering and advocation activity of its member and society surrounding the organization. DPO Mitra Sejahtera has a problem that its member has limitation in the usage of basic computer and office application, such as word processor and spreadsheet processor. Thus, Faculty of Information Technology, Duta Wacana Christian University conducted training for member of DPO Mitra Sejahtera. This training was held on March, 25-26 2019 in the DPO Mitra Sejahtera Head Office. The training gives a good result. Participants feels that the training is useful for them to help them understanding the basic function of word processing and spreadsheet processing.